Optimization of Irrigation Water to Maximize Transplanted Aman Rice Production in Selected Areas of Bangladesh - Yesmin, M S; Hossain, M B; Roy, D; Mahmud, M N H; Paul, P L C; Kundu, P K; Islam, M T (Bangladesh Rice Journal, 2023)
In rainfed and irrigated agriculture, optimization of irrigation scheduling is very essential to maximize the crop production using the limited of agricultural water resources. A study was conducted to estimate requirement of irrigation and its scheduling of T. Aman (wet season) rice in the Northwest and Southeast region of Bangladesh using CROPWAT model. This paper utilized the daily rainfall and reference evapotranspiration data sets, obtained from seven weather stations for the period of 1981 to 2015. Effective rainfall and reference crop evapotranspiration (ETo) were calculated using the USDA Soil Conservation method and Penman-Monteith method, respectively. The simulation model of this explored the appropriate transplanting date to utilize maximum rainwater and to avoid supplemental irrigation. Four transplanting dates 15 July, 30 July, 15 August and 30 August were considered for transplanting T. Aman rice in the study areas. The optimization results showed that the water requirement was lower of the rice crop transplanting on 15 July in all locations due to higher effective rainfall. No supplemental irrigation was required for T. Aman cultivation transplanted on 30 July in Rangpur, Dinajpur, Bogura and Mymensingh regions since rainfall was sufficient to meet the demand of the crop. Therefore, this period was found for suitable and recommended for transplanting of T. Aman rice in these four locations. Transplanting after 30 July in these four locations needed supplemental irrigations. This study also revealed that 30 July transplanting required one supplemental irrigation in Jashore and Rajshahi regions due to insufficient rainfall. This period was also considered as the appropriate transplanting time in these two locations. However, in Pabna, one supplemental irrigation must be applied for T. Aman even transplanting on 15 July owing to in adequate rainfall. Irrigation requirement and number of irrigations were gradually increased with delaying the transplanting time. Early transplanting demanded less irrigation than late transplanting. Bangladesh Rice J. 25 (2) : 11-20, 2021